Comparison Of External Beam Radiotherapy Followed By Intra-Luminal Brachytherapy With External Beam Radiotherapy Alone In Locally Advanced Carcinoma Of Esophagus. - Dar N.A, Qamer S,Malik T.R,Fir Afroz, Nayak B.G MD, Khan N.A , Sofi Mushtaq Ahmad, Malik M.H,Najmi A.M,; M.M, Lone (International Journal of Scientific Research and Management (IJSRM), 2017)
Aim: The aim was to compare the outcome of intraluminal boost brachytherapy following external beam radiotherapy with external beam radiotherapy alone in locally advanced carcinoma esophagus in terms of toxicity, response, andsurvival.Material and Methods: A total of 80 patients with squamous cell carcinoma of esophagus were enrolled in the study between June 2014 to June 2016.Patients were treated with external beam radiotherapy (EBRT) of 40 Gy by AP/PA portals with concurrent chemotherapy. After completion of first phase of EBRT patients were divided into two groups. In Group A, boost was given by intraluminal brachytherapy (ILBT) and in Group B, boost was given by 3 field technique of EBRT.Results: Out of 80 patients, 42 were males and 38 females in the age group of 51 – 70 years.  After completion of treatment, residual disease was present in 60 % and 77.5 % in Group A and B respectively. Complete response was seen in 22.5 % and 15 % in Group A and B respectively. Dysphagia improvement was seen in 86.5% and 59.9 % in Group A and B respectively (P= 0.45). Median survival was 57% and 43% in Group A and B respectively.Conclusions: Dysphagia improvement, local response and median survival was better and           toxicities less in Group A, as compared to Group B,